(untitled) (Ustozlar uchun, 2025)
In this article, not only the image of the mother but also the image of all the women in the world is reflected in a new perspective in the works of the well-known and famous O'tkir Hoshimov “Works of the world”, “Between two doors”. The image of the Mother in Oʻtkir Hoshimov's works symbolizes sincerity and kindness.